THE ROLE OF PUBLIC CONSCIOUSNESS AND CULTURE IN THE FORMATION OF KNOWLEDGE ABOUT MIGRATION - Boymirzaev Kabil Karimjonovich (Next Scientists Conferences, 2023)
The article examines the influence of public consciousness and culture on the formation of knowledge about migration. The authors analyze how the ideas and beliefs of society form stereotypes and perceptions of migrants, as well as influence the formation of socio-cultural norms regarding migration processes. The research highlights the role of language, mass media and socio-cultural institutions in the formation of images of migrants in the consciousness of society. The article also examines the relationship between public opinion and migration policy, emphasizing the importance of understanding cultural contexts for effective management of migration processes. The results of the study can serve as a basis for the development of strategies aimed at forming a more informed and tolerant public attitude towards migrants.